Analisis Partisipasi Masyarakat Terhadap Implementasi Perencanaan Strategis Di Kecamatan Rappocini - Kota Makassar (Analysis Of Public Participation To The Strategic Planning Implementation In Rappocini District - Makassar City) - Bihamding, Hariawan (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2018)
Based on the spirit of reform required a fundamental change in improving the welfare of society widely, it needs empowerment and support community involvement in development planning and implementation. Top-down development of paradigm in the centralized Orde Baru regime immediately changed with the issuance of Constitution No. 25 in 2004 about National Development Planning System, with the strengthening of aspiration and inclusion of stakeholders from the lowest level to the highest level. In order to optimize the implementation of development, one way that must be taken is strategic planning. During the 10 years of implementation, we need to know the extent to where public participation in the activity today. Therefore through this paper, the research objectives formulated to determine how public participation in the implementation of the strategic plan. This study also determined descriptive method study using a quantitative approach. And, by taking the locus of research in the Rappocini district, Makassar, it obtained analysis results that the level of public participation is relative to be good enough to the planning and implementation of strategic planning, but in terms of maintenance tends, it has the opposite results. In anticipation of these terms, it needs persuasive approaches to encourage more optimal public confidence in supporting the implementation of the development.